E-Banking Strategies and Financial Performance of Commercial Banks in Kenya - Chitai, Winnie; Wangari, Loise; Kamau, Beatrice; Mutua, Justice (International Journal of Finance and Accounting, 2024)
Purpose: Kenyan banks are rapidly adopting e-banking options like mobile banking and agent networks, driven by increased smartphone usage. While research suggests a link between e-banking and improved financial performance, a more nuanced understanding is needed. This study aimed to explore this connection in detail, considering various e-banking features and customer demographics, to provide valuable insights for Kenyan banks. This study explores the relationship between e-banking strategies and the financial performance of commercial banks in Kenya, acknowledging the sector's significant shift towards digital financial services. The research addresses the critical gap in understanding how specific e-banking features, adoption rates, and security measures influence financial outcomes. Methodology: The study employed a desktop research design, analysing existing data from sources like published research articles, industry reports, and central bank publications, to investigate the relationship between e-banking strategies and the financial performance of commercial banks in Kenya. The findings were presented in tables. Correlation and regression analysis was applied. Findings: Mobile banking in Kenya is set to continue its rapid growth, with adoption rates already exceeding 80%, as reported by the Central Bank of Kenya. User engagement is high, driven by features like money transfers, airtime top-ups, and bill payments, with banks such as Equity Bank, KCB, and Standard Chartered leading with robust mobile apps. Banks are also leveraging extensive agent networks to expand services to underbanked areas, promoting financial inclusion. Security and financial literacy initiatives are prioritized, with multi-factor authentication and transaction encryption utilized to build customer trust, underscored by studies showing a positive correlation (rho = 0.32, p-value < 0.01) between mobile banking usage and bank profitability. The positive impact on financial performance is evident through increased transaction volume and revenue growth, with agent banking contributing to deposit mobilization and cost efficiency, supported by research demonstrating a significant correlation (rho = 0.52, p-value < 0.01) between the number of agents and total deposits. Furthermore, financial literacy programs enhance customer trust (r = 0.53, p-value < 0.02), fostering long-term relationships and higher customer lifetime value. To capitalize on these findings, government authorities should facilitate policy frameworks, while commercial banks should invest in technology and expand banking networks. Educational institutions should integrate financial literacy into curricula, and NGOs can support community-based programs. International agencies should provide funding and technical assistance to promote financial inclusion and cybersecurity resilience. Unique Contribution to Theory, Practice and Policy: This study on e-banking strategies in Kenya offers significant contributions that extend beyond immediate findings, shedding light on theoretical considerations, practical applications for banks, and potential policy avenues. The study reinforces the value of integrating the Technology Acceptance Model (TAM) and Resource Dependence Theory (RDT) for a comprehensive understanding of e-banking adoption and performance, highlighting the role of financial literacy in user engagement. Practically, it emphasizes the importance of continuous innovation in mobile banking, strategic agent banking partnerships, and investments in security and financial literacy. Policy implications include the need for balanced data privacy regulations, government-supported financial literacy initiatives, and encouragement of data analytics for optimizing e-banking strategies. These insights aim to promote financial inclusion, trust, and long-term success for Kenyan banks and their customers.